2020
DOI: 10.1101/2020.07.21.20156711
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Healthcare Workers’ Mental Health and Wellbeing During the COVID-19 Pandemic in the UK: Contrasting Guidelines with Experiences in Practice

Abstract: Background Substantial evidence has highlighted the importance of considering healthcare workers′ (HCW) mental health during the COVID-19 pandemic, and several organisations have issued guidelines with recommendations. However, the definition of wellbeing and the evidence-base behind such guidelines remains unclear. Objectives Assessing the applicability of wellbeing guidelines in practice; identify unaddressed HCWs′ needs; and provide recommendations for supporting frontline staff during the current and futu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
0
14
0
1
Order By: Relevance
“…As the pandemic stretches into the future, and with the threat of further waves (possibly caused by mutant viral strains), it will be important to shift from crisis management to embedding new ways of working. This process should include seeking and listening to the views of frontline staff in determining what is important to them, 20 and including them in formal evaluations of new models of working, if we are to ensure a capable and resilient workforce who are enabled to continue to provide first-class care.…”
Section: Main Results and Implicationsmentioning
confidence: 99%
“…As the pandemic stretches into the future, and with the threat of further waves (possibly caused by mutant viral strains), it will be important to shift from crisis management to embedding new ways of working. This process should include seeking and listening to the views of frontline staff in determining what is important to them, 20 and including them in formal evaluations of new models of working, if we are to ensure a capable and resilient workforce who are enabled to continue to provide first-class care.…”
Section: Main Results and Implicationsmentioning
confidence: 99%
“…The available guidelines for psychosocial wellbeing during emergencies focus more on categorical definitions of distress and fail to tap into the resilience of the frontline workers. A study by San Juan et al (2020) contrasted guidelines with lived experiences of practicing HCWs in United Kingdom and reported that understaffing, mental exhaustion and busy schedules often prevented them from accessing the available interventions. Future research can focus on exploring the gaps in the current guidelines when compared to the unmet needs and perceptions of HCWs in India during the pandemic crisis.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare organisations should provide internal processes to maintain regular breaks for staff working in full PPE, even in contexts of understaffing and PPE shortages as these are key aspects of well-being. 64 The extra time needed for staff delivering care in full PPE should also be considered when assigning workloads. 54 Frequently changing guidance generated mistrust towards it.…”
Section: Discussionmentioning
confidence: 99%